Pengaruh Trust, User Experience, dan Perceived Ease of Use Terhadap Loyaitas Pengguna Pada Mahasiswa Aktif Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta - Farhan Fajar Sidiq; Gatot Nazir Ahmad; Diena Noviarini (Teewan Journal Solutions, 2026)
This study employs a descriptive quantitative approach to examine the influence of Trust (X1), User Experience (X2), and Perceived Ease of Use (X3) on the Loyalty of ShopeePay application users among students of the Faculty of Economics and Business at the State University of Jakarta, who also serve as the population in this research, totaling 5,375 students. Based on Hair et al.'s sampling method, the determined sample size for this study is 142 respondents. Data were collected through the distribution of questionnaires as research instruments, designed using a 6-point Likert scale. The data processing was carried out using the Statistical Product and Service Solutions (SPSS) software. The data analysis techniques applied in this study include: 1) validity and reliability tests, 2) classical assumption tests consisting of normality, heteroscedasticity, and multicollinearity tests, 3) multiple linear regression analysis, 4) hypothesis testing, including t-test and F-test, 5) coefficient of determination test. Based on the research results, it is shown that user experience has a significant positive effect on user loyalty, while trust and perceived ease of use do not have an effect on user loyalty. However, trust (X1), user experience (X2), and perceived ease of use (X3) have a simultaneous effect on user loyalty.